(untitled) (Herald of Journalism, 2019)
The beginning of children’s television broadcasting in independent Kazakhstan can be considered with the creation of the Balapan (Balapan) TV channel since September 27, 2010. The TV channel is included in the new media center «Kazamedia Ortaly» in Astana. It broadcasts 17 hours a day in Kazakh in SD format. All broadcasting is in Kazakh. These are programs like «Ol kim?», «Bul ne?», «Kulegesh», «Sen bilesin be?», «On sausak», «Sanjar men Kaisar», «Zholyn bolsyn balakhai!», «Bauyrsak», «Hello, Balapan!», «Sanam» and others. The list of themes of the programs shows that they are all playful, entertaining and cognitive, and all are thematically connected with the history and culture of the Kazakh people. Will it be fair to assume that broadcasting for children in Kazakhstan began only during the period of independence? The proposed article allows you to find out what the first Kazakh programs were like, what girls and boys dreamed of in the 60s and 70s, what programs were watched and what, believe that the historical discourse in the world of children’s television will make it possible to better know the history of Kazakhstan television for children.